2019
DOI: 10.2139/ssrn.3498358
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Wages over the Business Cycle in Worker-Owned Firms: Evidence from Spain

Abstract: † I am extremely grateful to my supervisor Ana Rute Cardoso for her continuous encouragement and advice. I would like to thank Gabriel Burdin, Caterina Gianetti, Paulo Guimaraes, Joan Llull, and participants at the Workshop on Social Economy for Young Economists in Forli, the Employee Share Ownership and Profit-Sharing Workshop in Berlin, and the ENTER PhD Jamboree in London for useful comments. Financial support from the Fundaciò Bancaria "La Caixa" under the Grant LCF/BQ/DE15/1036001 is gratefully acknowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They find that firms characterized by a higher degree of employee ownership exhibit, on average, better employment protection in the face of economy‐wide and firm‐specific negative shocks. Finally, in a recent paper, Garcia‐Louzao (2020) compare the job stability of non‐member employees in worker‐owned firms and IOFs in Spain. Their panel data analysis shows that during the 2008−13 financial and economic crisis, employment contraction in IOFs was four percentage points higher than that in worker‐owned co‐operatives, implying that co‐operatives can protect employment better when negative conditions prevail.…”
Section: The State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…They find that firms characterized by a higher degree of employee ownership exhibit, on average, better employment protection in the face of economy‐wide and firm‐specific negative shocks. Finally, in a recent paper, Garcia‐Louzao (2020) compare the job stability of non‐member employees in worker‐owned firms and IOFs in Spain. Their panel data analysis shows that during the 2008−13 financial and economic crisis, employment contraction in IOFs was four percentage points higher than that in worker‐owned co‐operatives, implying that co‐operatives can protect employment better when negative conditions prevail.…”
Section: The State Of the Artmentioning
confidence: 99%
“…In worker co‐operatives, job protection is a key requirement of the controlling stakeholder (Guest, 2002; Depedri et al., 2012; Navarra & Tortia, 2014). In other co‐operative types, employment stability is obtained as a by‐product of the fulfilment of members’ needs or as a form of positive reciprocity and solidarity between different non‐financial stakeholder groups (Garcia‐Louzao, 2020).…”
Section: The State Of the Artmentioning
confidence: 99%
“…Worker-owned cooperatives are structured to give workers a vote on their organization’s governance, and they explicitly prioritize workers’ interests, and often other social or environmental goals as well (Paranque & Willmott, 2014; Rothschild, 2009). Research has shown that, relative to traditional firms, cooperatives more often prioritize maintaining employment in times of financial stress and therefore help stabilize employment during crises (Delbono & Regianni, 2013; Garcia-Louzao, 2021). Recent research has also found that cooperative forms of organizing foster social trust (Sabatini, Modena, & Tortia, 2012), can make work less alienating (Kociatkiewicz, Kostera, & Parker, 2021), promote the values of collectivity, egalitarianism, and autonomy in a workforce, and create spaces in which diverse opinions can flourish and be productively debated (Kokkinidis, 2015).…”
Section: A Reality That Already Exists: Possibilities For More Democr...mentioning
confidence: 99%